Experiences and perceptions of people who use heroin: public health lessons from Hermosillo, Mexico - Silvia Magali Cuadra-Hernández; Sergio Salazar-Arriola; Armando Arredondo-López; María Beatriz Duarte-Gómez; Verónica Cuadra-Hernández; Celina Rueda-Neria (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2018)
Abstract: Heroin consumption in Mexico is low compared with its use in the United States; however, this practice is more common in the northern region of Mexico than in the rest of the country, being documented only in cities that are located exactly at the Mexico-U.S. border. The Mexican legal framework is focused on rehabilitation, but its effects on the lives of users are unknown. The objective of this research was to analyze how the regulatory Mexican framework is conceptualized and practiced in the daily life of a group of heroin users from a northern city, where consumption has recently spread and has not been documented. We collected the official registered data from users and conducted a qualitative study in Hermosillo, Sonora. A research on the legal framework was conducted, as well as on the city's context. Data on heroin users can be found at HIV health center, as there is no other source of such records. The Mexican legal framework aims at rehabilitation and at avoiding criminalization; however, the daily life of users drives them towards crime circuits: people commit crimes to stay in prison, where they can control the addiction and get heroin, in case of abstinence. The Mexican State has no empirical information to improve its programs and laws related to the use of heroin. The daily practices of users become not only epidemiological but social risks to the community and to the users themselves. Also, the lack of access due to stigmatization, criminalization and violence, increases the inequities, creating a cycle that reproduces poverty and suffering as part of a social structure. Therefore, changes are needed in the justice system.